Closer caregiver and care‐recipient relationships predict lower informal costs of dementia care: The Cache County Dementia Progression Study. Issue 8 (18th April 2016) - Rattinger, Gail B.; Fauth, Elizabeth B.; Behrens, Stephanie; Sanders, Chelsea; Schwartz, Sarah; Norton, Maria C.; Corcoran, Chris; Mullins, C. Daniel; Lyketsos, Constantine G.; Tschanz, JoAnn T.
Abstract: Introduction: Identifying factors associated with lower dementia care costs is essential. We examined whether two caregiver factors were associated with lower costs of informal care. Methods: A total of 271 care dyads of the Cache County Dementia Study were included. Estimates of informal costs were based on caregiver reports of time spent in care‐related activities and inflation‐adjusted 2012 Utah median hourly wages. Caregiver coping and emotional closeness with the care‐recipient were assessed using the Ways of Coping Checklist–Revised and Relationship Closeness Scale, respectively. Results: Higher closeness was associated with 24% lower costs (expβ = 0.763 [95% confidence interval: 0.583–0.999]) in linear mixed models controlling for demographics and baseline dementia severity and duration. Problem‐focused coping was not associated with informal costs ( P = .354). Discussion: Caregiver closeness, a potentially modifiable factor, predicted lower dementia informal care costs over time. Future studies examining the care environment in closer dyads may identify specific care‐related behaviors or strategies that are associated with lower costs.